2021
DOI: 10.1098/rspb.2021.0363
|View full text |Cite
|
Sign up to set email alerts
|

Agri-environment scheme nectar chemistry can suppress the social epidemiology of parasites in an important pollinator

Abstract: Emergent infectious diseases are one of the main drivers of species loss. Emergent infection with the microsporidian Nosema bombi has been implicated in the population and range declines of a suite of North American bumblebees, a group of important pollinators. Previous work has shown that phytochemicals found in pollen and nectar can negatively impact parasites in individuals, but how this relates to social epidemiology and by extension whether plants can be effectively used as pollina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Furthermore, across taxa, bees can vary in their ability to cope with NSMs, perhaps as a result of evolutionary history with specific plant taxa (Tiedeken et al., 2016). As interest grows in understanding the benefits of nectar and pollen secondary chemistry in agroecosystems (Adler et al., 2021; Folly et al., 2021; Fowler et al., 2020) or use in promoting pollination service (Arnold et al., 2021), our results suggest an important caveat, which is that systemic pesticides may alter these dynamics.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, across taxa, bees can vary in their ability to cope with NSMs, perhaps as a result of evolutionary history with specific plant taxa (Tiedeken et al., 2016). As interest grows in understanding the benefits of nectar and pollen secondary chemistry in agroecosystems (Adler et al., 2021; Folly et al., 2021; Fowler et al., 2020) or use in promoting pollination service (Arnold et al., 2021), our results suggest an important caveat, which is that systemic pesticides may alter these dynamics.…”
Section: Discussionmentioning
confidence: 81%
“…Caffeine, for example, in the nectar of plants such as Citrus, Coffea and Onobrychis (sainfoin) increases bee activity (e.g. Figure 2c), reduces parasite load (Folly et al., 2021) and promotes pollen transfer (Thomson et al., 2015). The addition of IMD, which B. impatiens workers do not show any preference for on its own (Muth et al., 2020), and which limits activity (Figure 2c,d), would likely result in lowered visitation rate with potential negative impacts on plant fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high degree of variability in antiparasitic effects found even among congeneric host species ( Fowler et al, 2022 ), there is a clear need to expand the scope of research to include a wider diversity of bee species. This need is particularly urgent in light of evidence that disease burden is associated with population declines, at least in bumble bees ( Averill et al, 2021 ; Cameron et al, 2011 ), and interest in using flowering species with demonstrated antiparasitic effects to reduce disease burden in wild bees ( Folly et al, 2021 ). To evaluate the utility of such approaches, we need to know how floral products influence disease in a wide range of bee species, and particularly those of conservation concern.…”
Section: The State Of the Fieldmentioning
confidence: 99%
“…Inhibitory effects of the same or related compounds also differ between target microorganisms. While caffeine is not biologically active against C. bombi ( Richardson et al, 2015 ), it inhibits a microsporidian parasite of bumble bees, Nosema bombi ( Folly et al, 2021 ), and the closely related N. ceranae, which infects honey bees ( Bernklau et al, 2019 ). Furthermore, variation in response to a compound across genotypes within a species provides an additional nuance to understanding bioactivity.…”
Section: Direct Chemical Effectsmentioning
confidence: 99%
See 1 more Smart Citation